HISTORY OF THE ORIGIN OF COMPUTER SCIENCE - Yuldashev Abdurauf Rozmatjonovich (Galaxy International Interdisciplinary Research Journal, 2023)
Computer science, an interdisciplinary field that encompasses the theory and practice of computing, has emerged as one of the most influential and rapidly evolving areas of study in the modern era. Its significance in shaping our technological advancements and driving innovation cannot be overstated. In this article, we delve into the captivating history of computer science, exploring its origins, key milestones, and the individuals who paved the way for this fascinating discipline.